Über den wissenschaftlichen Umgang mit den aramäischen Papyri und Ostraka von Elephantine - Joisten-Pruschke, Anke (Biblische Notizen, 2009)
In this essay the author reflects on Bezalel Porten’s approach to transcription in his Textbook of Aramaic Documents and – on this background – makes some general comments on the textual representation of the Papyri and Ostraca from Elephantine. In the following open questions concerning the Aramaic documents which have been discovered or rediscovered from the 1970s on. New combinations and re-arrangements of Papyrus fragments made by Bezalel Porten are listed and supplied with critical notes. Finally, using the example of Sachau-Papyrus 18, it is demonstrated that another look at the originals in the museums may lead to new conclusions.